Mechanisms Governing the Transfer of Pure and Plant Matrix Carotenoids Toward Emulsified Triglycerides. Issue 7 (5th February 2020) - Goupy, Pascale; Genot, Claude; Hammaz, Faiza; Halimi, Charlotte; Caris‐Veyrat, Catherine; Borel, Patrick
Abstract : Scope: The study aims to assess the role of factors assumed to be involved in the transfer of carotenoids from plant matrices to dietary emulsions in the upper digestive tract. Methods and Results: Transfer is first measured as a function of time of pure β‐carotene (βC), lutein (LUT), and lycopene (LYC) to triglyceride (TG) droplets dispersed in water. Then the transfer to TG droplets stabilized with either bovine serum albumin (BSA), phospholipids (PL), or both is measured. Finally, transfer of tomato and spinach puree carotenoids to these emulsions is measured. The maximal transfer efficiency of the pure carotenoids to uncoated emulsions is very efficient, ranging from 59% to 77%. However, it is dramatically impaired, ranging from 0.5% to 31% ( p  < 0.05), when emulsions are stabilized by the emulsifiers. Conversely, when LUT, and to a less extent βC, but not LYC, is provided by the vegetable purees, its maximal transfer efficiency is significantly higher for the coated emulsions than for the uncoated one. Conclusions: Emulsifiers can dramatically impair the transfer of pure carotenoids to emulsion TG while they can facilitate the transfer of carotenoids from plant matrices. This suggests that specific interactions between plant matrix compounds and emulsifiers can enhance the transfer efficiency of carotenoids. Abstract : Carotenoids are plant pigments assumed to have beneficial effects on health. However, only a small percentage is absorbed. It is hypothesized that one of the reasons is their low transfer efficiency from plant food matrices to the triglyceride phase of dietary emulsions. Therefore, the effect of two different emulsifiers and two different food matrices on their transfer efficiency is assessed.